In situ Raman and surface-enhanced Raman spectroscopy on working electrodes: spectroelectrochemical characterization of water oxidation electrocatalysts. Issue 33 (7th September 2015) - Joya, Khurram S.; Sala, Xavier
<x xml:space="preserve">Abstract</x> This perspective article gives an overview of the current developments regarding the use of in situ Raman and surface-enhanced Raman spectroscopy on working electrodes for probing the fate of molecular and heterogeneous catalysts during electrochemical water oxidation.